Analysis of Teacher Welfare in Indonesia and Developed Countries: A Comparative Study - Fatimah Az Zahrah; Muhammad Fiqri Syahril (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Teacher welfare is a strategic factor influencing professionalism, motivation, and educational quality, yet significant disparities remain between Indonesia and developed countries. Objective: This study compares teacher welfare in Indonesia with the United States and Australia to identify policy implications for improving educational quality. Method: A qualitative comparative approach was employed using semi structured interviews, focus group discussions, and document analysis of policy reports and scholarly publications. Data were analyzed through the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion verification. Results: The findings reveal that Indonesian teachers experience income disparities, unequal access to professional development, excessive administrative workloads, and limited psychological support. In contrast, the United States and Australia provide competitive salaries, structured career pathways, continuous professional development, mental health services, and work life balance policies. Conclusion: Indonesia should adopt a holistic teacher welfare framework integrating economic, professional, and psychological dimensions. Contribution: This study proposes a multidimensional comparative framework to support evidence based, sustainable, and inclusive teacher welfare policies while strengthening long term educational quality and teacher professionalism nationwide.